Preliminary design tasks for prototyping Self Sustaining Power Machines on Mars using local resources - Ferreiro Garcia, Ramon (JOURNAL OF ADVANCES IN PHYSICS, 2025)
This paper presents a preliminary design task to implement a group of machine prototypes capable of generating energy using the natural resources of Mars planet atmosphere. These prototypes are based on disruptive state of the art technologies particularly characterized by using pull forces achieved by cooling an appropriated thermal working fluid in the heat-work conversion interactions. Due to these groundbreaking characteristics, the machine functions as a hybrid isolated system. It operates both as an isolated system in relation to heat sources and sinks, and as a hybrid isolated system in its capacity to generate useful output energy for any energy-consuming application. This machine marks a significant advancement in combined cycles (CC), incorporating a Reversed Brayton Cycle (RBC) and a Self-Sustaining Power Machine (SSPM) of this kind. By combining these thermal engines, the technology enables operation without reliance on either an external heat source or heat sink, challenging traditional thermodynamic principles. A group of prototypes design tasks based on the case study considers a combined cycle (CC) based on the combination of a heat pump consisting of a reverse Brayton cycle and a self-sustaining power machine (SSPM) is proposed to demonstrate these capabilities. The CC prototype consisting of a RBC and a SSPM was evaluated through the referred case study with argon for the RBC while using argon, air, nitrogen, and carbon dioxide as real thermal working fluids (TWFs) for the cascaded PUs of the SSPM. Results depicted in Tables 16-18-20-22 and 23 indicate that the proposed CC operating equipped with a SSPMs composed by 6 PUs operating on a VsVs cycle achieved a total acceptable amounts of self-sufficient output net work.